Forests at the land-atmosphere interface - Mencuccini, M.; Grace, J.; Grace, J.; McNaughton, K. G.; McNaughton, K. G.; Mencuccini, M.; Moncrieff, J.; Moncrieff, J. (Wallingford :CABI Publishing, 2004)
This book contains 17 chapters on the biophysical processes occurring at the interface between forest ecosystems and the atmosphere. It brings together topics such as the role of stomata in regulating water fluxes to the atmosphere, radiation penetration into forest canopies, forest meteorology, mesoscale modelling, remote sensing of canopy characteristics of forests, neural network predictions of carbon sequestration in Europe, and policy making and forestry. This book also celebrates the achievements of Professor Paul Jarvis, a highly distinguished environmental biologist and forest physiologist, who devoted his career to understanding these relationships. The individual chapters are based on papers presented at the meeting Forests at the Land-Atmosphere Interface, which was held in his honour at the University of Edinburgh on 17-19 September 2001. This book will be of significant interest to researchers in forestry, ecology, environmental sciences and natural resources.
Keywords: EE112 - Forestry Economics, (New March 2000); EE120 - Policy and Planning; FF062 - Plant Water Relations; KK100 - Forests and Forest Trees (Biology and Ecology); KK110 - Silviculture and Forest Management; PP500 - Meteorology and Climate; ZZ100 - Mathematics and Statistics; ZZ900 - Techniques and Methodology; Europe